The effect of a community nursing model for smoke-free home on quit smoking in family - Suteerangkul, Peraya; Rawiworrakul, Tassanee; Kalampakorn, Surintorn; Saradhuldhat, Galaya; Addjanagitti, Patcharin; Panupas, Thapanee (Thai Journal of Nursing, 2023)
This study aims to examine the effects of a community nursing model for smoke-free home on quit smoking in the pilot community at Thanyaburi District, Pathum Thani Province. The smoke-free home program comprises family assessment, family support with positive reinforcement to quit smoking, reminder of the no smoking rule, home environment improvement, brief advice for quit smoking by nurses, providing community support and monitoring, and referring to community hospital or quit line 1600. Data collection was performed using the nicotine dependence test, and piCO Smokerlyzer for exhaled carbonmanoxide measurement. Descriptive statistics, and repeated measures ANOVA were employed for data analysis. The smoker of 122, are males (88.5%) and females (11.5%) aged 18-83 years old (M = 44.15, SD = 16.56), mostly used factory cigarettes (83.6 %), following by hand-rolled cigarettes (13.4 %) and both types of cigarettes (3.3 %). The community nursing model for smoke-free home could help smokers continuously quit smoking for 6 months (12.3%), and represented smoke-free homes (77.05%). Mean difference test for nicotine addiction level before and after the program implementation at the 1st, 3rd, and 6th month reveal statistically significances at p < .01 (F = 21.663).